Screening of ten plant species for metaphase chromosome preparation in adult mosquitoes (Diptera: Culicidae) using an inoculation technique - Jitpakdi A. (2014)
The screening of 10 plant species (Aloe barbadensis Mill., Asparagus officinalis L., As. plumosus Bak., As. racemosus Willd., As. sprengeri Regel, Codyline fruticosa Goppert, Dracaena loureiri Gagnep., Gloriosa superba L., Hemerocallis flava L., and Sansevieria cylindrica Bojer) for colchicine-like substance(s) using a mosquito cytogenetic assay revealed that a 1% solution of dried Gl. superba rhizome extracted in 0.85% sodium chloride solution could be used instead of a 1% colchicine in Hanks' balanced salt solution. The metaphase rates and average number of metaphase chromosomes per positive mosquito of Aedes aegypti (L.) after intrathoracic inoculation with 1% Gl. superba-extracted solution were 100% and 29.80 in females, and 90% and 25.78 in males, whereas the inoculation with 1% colchicine solution yielded 100 and 90% metaphase rates, and 20.90 and 12.22 average number of metaphase chromosomes per positive mosquito in females and males, respectively. The application of Gl. superba-extracted solution for metaphase chromosome preparation in other mosquito genera and species [e.g., Culex quinquefasciatus Say, Toxorhynchites splendens (Wiedemann), and Anopheles vagus (Döenitz)] also has yielded the satisfactory results.